The condition of cervical tooth wear and association with brushing habits among students of Hue University of Medicine and Pharmacy - Le, Thi Quynh Thu; Huynh, Thi Hue Chi; Nguyen, Ngoc Tam Dan (Tạp chí Y Dược Huế, 2023)
Background: Cervical tooth wear is a common oral health issue that often leads to the loss of tooth structure integrity, making the teeth sensitive, prone to plaque buildup, affecting the dental pulp, and causing aesthetic concerns. Assessing the extent of tooth erosion and its correlation with brushing habits is crucial for enhancing the effectiveness of necessary interventions and preventive measures. Objective: To determine the prevalence and severity of cervical tooth wear in young individuals aged 18-25 and examine the association between brushing habits and cervical tooth wear. Methods: A cross-sectional descriptive study was conducted on 60 undergraduate students from the Hue University of Medicine and Pharmacy, aged 18 - 25, who visited the Odonto-Stomatology Clinic, Family Medicine Center from November 2020 to April 2021. Study participants were interviewed and provided clinical examinations after obtaining their consent. Results: The study findings revealed a relatively high prevalence of cervical tooth wear (53.3%). Most cases exhibited a severity score 0 (no tooth wear), and no cases were classified as score 4. The highest prevalence of cervical tooth wear was observed in the left mandibular (65.6%). Regarding the association between cervical tooth wear and brushing habits, there was a significant correlation between horizontal brushing technique and brush hardness with cervical tooth wear (p < 0.05). However, there was no significant correlation between brushing frequency, toothbrush replacement time, brushing duration, and force applied during brushing with cervical tooth wear (p > 0.05). Conclusion: In general, the prevalence of cervical tooth wear is relatively high, and there exists a correlation between horizontal tooth brushing habits and brush hardness with the condition of cervical tooth wear. Therefore, implementing preventive measures against cervical tooth wear is crucial for enhancing oral health for everyone.